Discussing health risk behaviors in parent-child communication influences on communicative competence - Jabal, Ronaldo F.; Paradina, Katrina Paulette T. (2010)
This study analyzes the amount of influence that age, sex, educational attainment, socio-economic status (SES) and religion contribute to the communicative competence of individuals in discussing certain types of health risk behaviors. Competence is a product of social experience or is highly dependent on the context in which the interaction takes place. Through secondary data analysis, this study examines competency levels in discussing smoking, drugs, alcohol and sex and correlates them with the parent's age, sex, educational attainment, SES and religion. Results show that some selected variables are associated with communicative competence, although mostly weak. The parent's sex, age, and education are not significantly predictive of communication competence in discussing smoking, drugs, and alcohol, but there are significant differences on the basis of SES. Competencies to discuss sex vary. The results of the study are useful to those who seek to minimize health risk behaviors through the development of strategic communication campaign plans and programs.